Electric field assisted plasma modified pressure responsive seepage conductive pre-lithiation reagent, preparation method and application thereof

CN122992070APending Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611204945.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有Li5AlO4基预锂化试剂制备工艺中掺杂不均匀、无压力导电响应、晶格结构不可控、成品导电性差、补锂效率低的技术缺陷,本发明提供了一种电场辅助等离子改性压力响应型渗流导电预锂化试剂及其制备方法和应用

Benefits of technology

(1)工艺独创性高:本发明采用预极化+脉冲低温等离子球磨+微负压低温稳晶三道独有工序,区别于传统普通球磨,工艺差异化明显,生成的晶格畸变可控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992070A_ABST
    Figure CN122992070A_ABST
Patent Text Reader

Abstract

The application discloses an electric field assisted plasma modified pressure response type seepage conductive prelithiation reagent and a preparation method and application thereof, and belongs to the technical field of functional lithium supplementing material preparation of lithium ion batteries. The Li5AlO4-based prelithiation reagent with controllable lattice distortion and three-dimensional seepage conductive network is prepared by relying on a unique pre-polarization + pulsed low-temperature plasma ball milling + micro-negative pressure low-temperature crystal stabilization treatment process, and the Li5AlO4 pressure controllable conductive is realized. The anode prelithiation is carried out by using the prepared Li5AlO4, so that the battery polarization can be reduced, and the first circle lithium loss compensation rate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery functional lithium replenishment material preparation technology, specifically relating to an electric field-assisted plasma modified pressure-responsive percolation conductive pre-lithiation reagent, its preparation method and application. Background Technology

[0002] During the first charge and discharge cycle of a lithium-ion battery, a solid electrolyte interphase (SEI) film forms on the surface of the negative electrode. This process irreversibly consumes active lithium ions inside the battery, causing capacity decay in the first cycle and reducing the battery's energy density and cycle life. Positive electrode pre-lithiation is the mainstream technology for compensating for irreversible lithium loss and improving battery capacity.

[0003] Li5AlO4 is an excellent inorganic pre-lithiation material due to its high lithium content and good chemical stability. However, existing technologies have significant drawbacks: pure-phase Li5AlO4 has high insulation, poor lattice conductivity, and high delithiation potential; traditional synthesis processes result in many impurities and severe lithium volatilization; and ordinary mechanical ball milling doping methods have high randomness and poor uniformity, making it impossible to form a stable grain boundary conductive network.

[0004] At present, most of the modification processes adopt ordinary mechanical ball milling combined with high temperature annealing. The process is highly homogenized and has the following disadvantages: (1) Conventional ball milling relies only on mechanical impact and cannot accurately construct controllable lattice distortion. The material does not have pressure conductivity response characteristics; (2) High temperature annealing easily destroys the fine grain boundary structure, resulting in coarse grains and poor conductivity; (3) There is no powder activation process, resulting in fewer doping sites and uneven doping; (4) There is no lattice locking process, resulting in large residual stress inside the material and poor structural stability.

[0005] In summary, the existing Li5AlO4 preparation process produces Li5AlO4 with uneven doping, no pressure conductivity response, uncontrollable crystal structure, poor conductivity, and low lithium replenishment efficiency, which is difficult to meet the industrial lithium replenishment requirements of high-stability lithium batteries. Therefore, it is urgent to develop a high-performance pressure-responsive pre-lithiation reagent. Summary of the Invention

[0006] To address the technical shortcomings of existing Li5AlO4-based pre-lithiation reagent preparation processes, such as uneven doping, lack of pressure conductivity response, uncontrollable crystal structure, poor conductivity of finished products, and low lithium replenishment efficiency, this invention provides an electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent, its preparation method, and its applications. This invention utilizes a unique pre-polarization + pulsed low-temperature plasma ball milling + micro-negative pressure low-temperature crystal stabilization process to prepare a Li5AlO4-based pre-lithiation reagent with controllable lattice distortion and a three-dimensional percolation conductive network, achieving pressure-controllable conductivity of Li5AlO4. Using the Li5AlO4 prepared by this invention for positive electrode pre-lithiation can reduce battery polarization and improve the first-cycle lithium loss compensation rate.

[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for preparing an electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent, comprising the following steps: Pure phase Li5AlO4 was pre-polarized under an inert atmosphere. The pre-polarized pure phase Li5AlO4 was mixed with a cobalt source and boric acid was added as a grain boundary passivation aid. The mixture was then subjected to pulsed low-temperature plasma ball milling. The powder after pulsed low-temperature plasma ball milling was subjected to low-temperature crystal stabilization under micro-negative pressure to obtain the electric field-assisted plasma modified pressure-responsive percolation conductive pre-lithiation reagent. The pre-polarization polarization voltage is 450~600V, and the polarization time is 6~12min; The conditions for pulsed low-temperature plasma ball milling are: plasma discharge voltage 5~30kV, pulse current 10~100mA, frequency 5~10kHz, intermittent ball milling, and temperature ≤40℃ throughout the process. The conditions for low-temperature crystal stabilization under micro-negative pressure are: temperature 120~160℃, pressure -0.07~-0.03MPa, and heat preservation for 2~4h.

[0008] The pure-phase Li5AlO4 is pre-polarized (to enrich the powder with negative charges and construct activation sites), pulsed low-temperature plasma ball milling (to complete in-situ lattice doping of cobalt using electric field coupled mechanical force), and micro-negative pressure low-temperature crystal stabilization (to lock lattice distortion and eliminate residual internal stress without lattice annealing and recrystallization). Co in the Co source is then converted into Co... 2+ or Co 3+ The form selectively occupies Li or Al sites, and the doping substitution is a pure lattice substitution with no elemental cobalt or impurity phase precipitation. Moreover, the Co doped phase continuously overlaps and connects with each other at the grain boundaries of Li5AlO4 grains, constructing a through-type three-dimensional percolation conductive network. Relying on the artificially controllable lattice distortion structure induced by the plasma electric field, the pre-lithiation reagent has pressure-dependent percolation conductivity characteristics. That is, under normal temperature and pressure test conditions, as the compaction stress increases, the degree of lattice distortion decreases, the conductive path becomes more compact, and the conductivity increases monotonically with the increase of the compaction pressure.

[0009] Preferably, the pure phase Li5AlO4 is prepared by ball milling and sintering using lithium source and aluminum source as raw materials, combined with sintering aid.

[0010] More preferably, the lithium source includes at least one of Li2O, LiOH, LiOH·H2O, Li2CO3 and LiNO3; the aluminum source includes at least one of Al2O3, Al(OH)3 and Al(NO3)3·9H2O; and the sintering aid is anhydrous lithium fluoride (LiF).

[0011] This invention uses LiF to reduce the sintering activation energy, boric acid to passivate grain boundaries, and two additives to synergistically suppress the formation of impurity phases and lock the distorted lattice.

[0012] More preferably, the lithium-aluminum molar ratio of the lithium source to the aluminum source is 5.01~5.1:1; the amount of the sintering aid added is 0.15~0.6% of the total mass of the lithium source and the aluminum source; and the ball milling media is zirconia balls with a ball-to-material mass ratio of 8~15:1.

[0013] More preferably, the sintering is a three-stage sintering under an inert atmosphere, with a temperature gradient of 450℃ for 8~12h, 600℃ for 8~12h, and 800℃ for 60~80h.

[0014] Preferably, the ball milling speed is 400~1400 rpm, the ball milling time is 3~24h, and the machine stops for 5min after every 30min of ball milling.

[0015] Preferably, the cobalt source includes LiCoO2, CoO, Co3O4, and LiNi. x Co y Al z O2 and LiNi x Co y Mn z At least one of O2; the LiNi x Co y Al z O2 and the LiNi x Co y Mn z In O2, 0.30≤x≤0.99, 0.01≤y≤0.40, and 0.00≤z≤0.40.

[0016] Preferably, the mass ratio of the pre-polarized pure phase Li5AlO4 to the cobalt source is 2~10:1.

[0017] Preferably, the amount of boric acid is 0.05~0.3% of the total mass of the pre-polarized pure phase Li5AlO4 and the cobalt source.

[0018] The second technical solution of the present invention provides an electric field-assisted plasma-modified pressure-responsive percolation conductive prelithiation reagent prepared according to the above-mentioned preparation method of electric field-assisted plasma-modified pressure-responsive percolation conductive prelithiation reagent.

[0019] The third technical solution of the present invention provides a lithium-supplemented positive electrode sheet, the components of which include positive electrode active material and the above-mentioned electric field-assisted plasma modified pressure-responsive percolation conductive pre-lithiation reagent.

[0020] Preferably, the mass percentage of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent is 1-15%.

[0021] Preferably, the positive electrode active material includes LiCoO2 and LiNi. x Co y Mn z O2, LiNi x Co y Al z O2 or LiFePO4; the LiNi x Co y Al z O2 and the LiNi x Co y Mn z In O2, 0.30≤x≤0.99, 0.01≤y≤0.40, and 0.00≤z≤0.40.

[0022] The fourth technical solution of the present invention provides the application of the above-mentioned electric field-assisted plasma modified pressure-responsive percolation conductive pre-lithiation reagent or the above-mentioned lithium-replenishing positive electrode sheet in the preparation of lithium batteries.

[0023] The beneficial technical effects of the present invention are as follows: (1) High process originality: The present invention adopts three unique processes: pre-polarization + pulsed low-temperature plasma ball milling + micro negative pressure low-temperature crystal stabilization, which are different from traditional ball milling. The process is significantly different and the resulting lattice distortion is controllable.

[0024] (2) Excellent electrical conductivity of the material: In the pressure range of 5~30MPa, the conductivity of the material provided by the present invention is increased from 0.02nS / cm to more than 0.075nS / cm, with strong pressure sensitivity and more compact conductive path after the electrode is compacted.

[0025] (3) Excellent doping effect: Cobalt is doped in the form of lattice substitution, with no elemental cobalt precipitation. The thickness of the doped phase is 5~50nm, forming a gradient coating and connection structure.

[0026] (4) Excellent electrochemical performance: The material provided by this invention is stable and irreversibly delithiated at 3.0~4.6V, and the lithium loss compensation rate of the battery in the first cycle can reach more than 91%, which can effectively reduce battery polarization. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a schematic diagram of the microstructure of the modified Li5AlO4 powder prepared for Comparative Example 1.

[0029] Figure 2 This is a schematic diagram of the microstructure of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0030] Figure 3 Conductivity-pressure response curves of pure phase Li5AlO4 powder, modified Li5AlO4 powder prepared in Comparative Example 1, and pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0031] Figure 4 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0032] Figure 5 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0033] Figure 6 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 1 is shown.

[0034] Figure 7 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 2.

[0035] Figure 8 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 2.

[0036] Figure 9 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 2 is shown.

[0037] Figure 10 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 3.

[0038] Figure 11 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 3.

[0039] Figure 12 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 3 is shown.

[0040] Figure 13 The conductivity-pressure response curve of the modified Li5AlO4 powder prepared for Comparative Example 1.

[0041] Figure 14 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Comparative Example 1 is shown.

[0042] Figure 15 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Comparative Example 2 is shown.

[0043] Figure 16 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared for Comparative Example 2.

[0044] Figure 17 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Comparative Example 2 is shown. Detailed Implementation

[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0046] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0047] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0048] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.

[0049] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0050] Example 1 S1. LiOH·H2O was selected as the lithium source and Al(OH)3 as the aluminum source, with a lithium-aluminum molar ratio of 5.02:1; 0.35% anhydrous LiF was added in total mass of lithium and aluminum sources; ball milling parameters: zirconia balls, ball-to-material mass ratio of 10:1, ball milling at 600 rpm for 3 hours, and premixed ball milling under argon protection. The powders obtained from ball milling S2 and S1 are dried in stages by vacuum gradient heating to remove moisture; S3, Three-stage sintering: The powder obtained from S2 drying is kept at 450℃ for 10h, 600℃ for 10h, and 800℃ for 70h to obtain pure phase Li5AlO4 powder. S4. Pre-polarization: Pure phase Li5AlO4 powder is pre-polarized with a polarization voltage of 500V and a processing time of 9min to obtain pre-polarized pure phase Li5AlO4 powder. S5. Pulse Low-Temperature Plasma Ball Milling: CoO was selected as the cobalt source. The mass ratio of prepolarized pure phase Li5AlO4 powder to CoO was 5:1. 0.15wt% boric acid was added to the mixed powder for pulse low-temperature plasma ball milling. Plasma parameters: voltage 12kV, current 45mA, frequency 7kHz; ball milling parameters: stainless steel balls, ball-to-material mass ratio 15:1, ball milling speed 600rpm, ball milling for 12 hours, with a 5-minute stop every 30 minutes of ball milling; the entire process temperature did not exceed 40℃; plasma prepolarized Li5AlO4 powder was obtained. S6. Low-temperature stable crystal under micro-negative pressure: The plasma prepolarized Li5AlO4 powder obtained in S5 was kept under negative pressure at 140℃ and -0.05MPa for 3h to obtain pressure-responsive permeation conductive Li5AlO4 powder.

[0051] Example 2 S1. Li2CO3 was selected as the lithium source and Al2O3 as the aluminum source, with a lithium-aluminum molar ratio of 5.05:1; 0.25% anhydrous LiF was added in total mass of lithium and aluminum sources; ball milling parameters: zirconia balls, ball-to-material mass ratio of 12:1, ball milling at 700 rpm for 2 hours, and premixed ball milling under argon protection. The powders obtained from ball milling S2 and S1 are dried in stages by vacuum gradient heating to remove moisture; S3, Three-stage sintering: The powder obtained from S2 drying is kept at 450℃ for 8h, 600℃ for 12h, and 800℃ for 65h to obtain pure phase Li5AlO4 powder. S4. Pre-polarization: Pure phase Li5AlO4 powder is pre-polarized with a polarization voltage of 550V and a processing time of 7min to obtain pre-polarized pure phase Li5AlO4 powder. S5. Pulse Low-Temperature Plasma Ball Milling: LiCoO2 was used as the cobalt source. The mass ratio of prepolarized pure phase Li5AlO4 powder to LiCoO2 was 5:1. 0.20wt% boric acid was added to the mixed powder for pulse low-temperature plasma ball milling. Plasma parameters: voltage 18kV, current 60mA, frequency 9kHz; ball milling parameters: stainless steel balls, ball-to-material mass ratio 20:1, ball milling speed 750rpm, ball milling for 8 hours, with a 5-minute stop after every 30 minutes of ball milling; the entire process temperature did not exceed 40℃; plasma prepolarized Li5AlO4 powder was obtained. S6. Low-temperature stable crystal under micro-negative pressure: The plasma prepolarized Li5AlO4 powder obtained in S5 was kept under negative pressure at 130℃ and -0.04MPa for 2.5h to obtain pressure-responsive permeation conductive Li5AlO4 powder.

[0052] Example 3 S1. LiNO3 was selected as the lithium source and Al(NO3)3·9H2O as the aluminum source, with a lithium-aluminum molar ratio of 5.08:1; 0.50% anhydrous LiF was added in total mass of lithium and aluminum sources; ball milling parameters: zirconia balls, ball-to-material mass ratio of 14:1, ball milling at 700 rpm for 2 hours, and premixed ball milling under argon protection. The powders obtained from ball milling S2 and S1 are dried in stages by vacuum gradient heating to remove moisture; S3, Three-stage sintering: The powder obtained from S2 drying is kept at 450℃ for 12h, 600℃ for 9h, and 800℃ for 75h to obtain pure phase Li5AlO4 powder. S4. Pre-polarization: Pure phase Li5AlO4 powder is pre-polarized with a polarization voltage of 580V and a processing time of 11min to obtain pre-polarized pure phase Li5AlO4 powder. S5. Pulse Low-Temperature Plasma Ball Milling: Co3O4 was used as the cobalt source. The mass ratio of prepolarized pure phase Li5AlO4 powder to Co3O4 was 3:1. 0.28wt% boric acid was added to the mixed powder for pulse low-temperature plasma ball milling. Plasma parameters: voltage 25kV, current 80mA, frequency 5.5kHz; ball milling parameters: stainless steel balls, ball-to-material mass ratio 20:1, ball milling speed 1000rpm, ball milling for 18h, with a 5min stop every 30min of ball milling; the entire process temperature did not exceed 40℃; plasma prepolarized Li5AlO4 powder was obtained. S6. Low-temperature stable crystal under micro-negative pressure: The plasma prepolarized Li5AlO4 powder obtained in S5 was kept under negative pressure at 150℃ and -0.06MPa for 3.5h to obtain pressure-responsive permeation conductive Li5AlO4 powder.

[0053] Comparative Example 1 Modified Li5AlO4 powder was prepared by using ordinary mechanical ball milling without pre-polarization, pulsed low-temperature plasma ball milling, or micro-negative pressure low-temperature crystal stabilization treatment, with the addition of LiF and boric acid additives, and the remaining raw materials and sintering conditions being the same as in Example 1.

[0054] Comparative Example 2 Without adding LiF and boric acid additives, and with the remaining raw materials and preparation steps being the same as in Example 1, pressure-responsive percolation conductive Li5AlO4 powder was obtained.

[0055] Figure 1 This is a schematic diagram of the microstructure of the modified Li5AlO4 powder prepared for Comparative Example 1.

[0056] from Figure 1 SEM and TEM images of modified Li5AlO4 powder obtained by traditional ball milling show that traditional mechanical ball milling relies solely on mechanical collision energy input and lacks the pre-activation effect of plasma electric field on the powder surface, thus failing to construct the charge-rich activation sites generated by the pre-polarization step of this invention. Under these conditions, even with the introduction of Co-containing raw materials, mechanical force is insufficient to drive Co. 2+ / Co 3+ Effective lattice occupancy across phase interfaces cannot promote selective enrichment at grain boundaries. On the contrary, excessive mechanical shearing leads to a rapid refinement of Li5AlO4 grains to the nanoscale, resulting in the collapse of long-range order and the formation of a high-density polycrystalline and amorphous mixed phase. At grain boundaries, atomic coordination is highly unsaturated, generating numerous deep-level defect states that form strong scattering and recombination centers for charge carriers. Simultaneously, due to the lack of electron hopping channels provided by variable-valence Co centers, the conductivity decreases rather than increases, remaining at 10-10. -6 The insulating behavior on the order of S / cm, independent of the pressing pressure, confirms that traditional ball milling only achieves structural disorder but fails to construct a functional percolation conductive network.

[0057] Figure 2 This is a schematic diagram of the microstructure of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0058] Depend on Figure 2 It is known that, compared to traditional ball milling which can only achieve structural disorder, this invention uses pre-polarization to perform surface activation treatment on Li5AlO4 powder. Plasma bombardment enriches the powder surface with negative charges and constructs high-density defect activation sites, significantly reducing the activation energy barrier for Co cross-phase migration. Subsequently, pulsed low-temperature plasma ball milling applies a synergistic coupling effect of electric field and mechanical force, driving Co... 2+ / Co 3+By overcoming the limitations of thermodynamic equilibrium, in-situ doping into the Li5AlO4 lattice was achieved. This non-equilibrium process preferentially and selectively enriches Co at grain boundaries, forming a lattice distortion transition region with a thickness of 5-50 nm, thus constructing a unique core-shell heterostructure: the core is a lattice-complete Li5AlO4 matrix, the middle layer is a Co-doped lattice distortion region, and the outer shell is a Co-enriched phase that is interconnected at the grain boundaries.

[0059] Figure 3 Conductivity-pressure response curves of pure phase Li5AlO4 powder (LAO), modified Li5AlO4 powder prepared in Comparative Example 1, and pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0060] from Figure 3 As can be seen, the conductivity of pure-phase Li5AlO4 powder is maintained at only about 10 due to the intrinsic limitation of the wide bandgap of antifluorite. -2 The concentration of Co in Li5AlO4 is on the order of nS / cm, with only a slight increase in pressure. While conventional ball milling introduces grain boundary passivators, the lack of pre-activation of the powder surface by the plasma electric field prevents the construction of effective Co migration channels. Mechanical shearing only refines the grains to a polycrystalline / amorphous mixed state. Grain boundary defect states strongly scatter and recombine charge carriers, causing the conductivity to drop to near zero and completely lose its pressure response. This confirms that simple mechanical refinement and passivator addition cannot overcome the insulating nature of Li5AlO4. In contrast, after pre-polarization activation and pulsed low-temperature plasma ball milling with a combined electric field and mechanical force, Co... 2+ / Co 3+ Selective enrichment and interconnection at grain boundaries constitute a three-dimensional percolating conductive network. This network gradually becomes interconnected under pressure of 5–30 MPa as particle contact is optimized, with conductivity monotonically increasing from 0.025 nS / cm to over 0.078 nS / cm, exhibiting significant pressure-dependent percolating conductive characteristics. This is approximately 4 times higher than that of pure-phase Li5AlO4 powder and more than 2 orders of magnitude higher than that of ordinary ball-milled products, directly demonstrating the role of the plasma electric field-assisted strategy in activating the electronic transport function of Li5AlO4.

[0061] Figure 4 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0062] Figure 5 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 1.

[0063] from Figure 5 As can be seen, the conductivity of the material after plasma electric field-assisted modification is 0.023 nS / cm at 5 MPa and 0.083 nS / cm at 30 MPa.

[0064] Figure 6 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 1 is shown.

[0065] The specific steps for assembling a lithium battery are as follows: The prepared Li5AlO4 material is ground with acetylene black in a mortar. Then, N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) are added to dissolve the mixture (material:acetylene black:PVDF mass ratio 70:20:10). The resulting slurry is then uniformly coated onto aluminum foil and subsequently dried in a vacuum oven at 120℃ for at least 12 hours. The dried electrode sheets are cut into 13mm diameter discs to serve as the positive electrode for assembling the half-cell. The negative electrode uses a 13mm diameter lithium sheet, and the battery casing is a Cr2025 type. A conventional high-voltage resistant electrolyte is used, suitable for the 3.0~4.6V testing requirements. The assembly is then performed in the following order from bottom to top: positive electrode casing, positive electrode sheet, separator, lithium sheet, nickel foam, and negative electrode casing. The first charge-discharge performance of a half-cell was tested using the LAND battery testing system at a voltage range of 3.0~4.6V and a rate of 1C (180mA / g).

[0066] The assembly steps for battery testing in subsequent embodiments or comparative examples are the same as above.

[0067] from Figure 6 As can be seen, the first-charge specific capacity of the prepared lithium battery reaches approximately 550 mAh / g at 4.6V and approximately 760 mAh / g at 4.8V. Compared with the original Li5AlO4 material, the modified material has a lower voltage plateau, while exhibiting a higher and irreversible first-charge specific capacity. It is a very promising pre-lithiation reagent.

[0068] Figure 7 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 2.

[0069] Figure 8 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 2.

[0070] from Figure 8 As can be seen, the conductivity of the material after plasma electric field-assisted modification is 0.021 nS / cm at 5 MPa and 0.080 nS / cm at 30 MPa.

[0071] Figure 9 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 2 is shown.

[0072] from Figure 9As can be seen, the first-charge specific capacity of the prepared lithium battery reaches approximately 510 mAh / g at 4.6V and approximately 880 mAh / g at 4.8V. Compared with the original Li5AlO4 material, the modified material has a lower voltage plateau, while exhibiting a higher and irreversible first-charge specific capacity. It is a very promising pre-lithiation reagent.

[0073] Figure 10 The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 3.

[0074] Figure 11 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Example 3.

[0075] from Figure 11 As can be seen, the conductivity of the material after plasma electric field-assisted modification is 0.020 nS / cm at 5 MPa and 0.090 nS / cm at 30 MPa.

[0076] Figure 12 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Example 3 is shown.

[0077] from Figure 12 As can be seen, the first-charge specific capacity of the prepared lithium battery reaches approximately 500 mAh / g at 4.6V and approximately 780 mAh / g at 4.8V. Compared with the original Li5AlO4 material, the modified material has a lower voltage plateau, while exhibiting a higher and irreversible first-charge specific capacity. It is a very promising pre-lithiation reagent.

[0078] Figure 13 The conductivity-pressure response curve of the modified Li5AlO4 powder prepared for Comparative Example 1.

[0079] from Figure 13 As can be seen, the material exhibits no pressure conductivity response, with a conductivity of only 0.008 nS / cm at 30 MPa.

[0080] Figure 14 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Comparative Example 1 is shown.

[0081] from Figure 14 As can be seen, the first-charge specific capacity of the prepared lithium battery is only about 30 mAh / g at 4.6V and only about 370 mAh / g at 4.8V.

[0082] Figure 15The XRD pattern of the pressure-responsive percolation conductive Li5AlO4 powder prepared in Comparative Example 2 is shown.

[0083] Figure 16 The conductivity-pressure response curve of the pressure-responsive percolation conductive Li5AlO4 powder prepared for Comparative Example 2.

[0084] from Figure 16 As can be seen, the material modified by plasma electric field has a pressure conductivity response, with a conductivity of 0.0150 nS / cm at 5 MPa and 0.065 nS / cm at 30 MPa.

[0085] Figure 17 The first charge-discharge curve of the lithium battery prepared using the pressure-responsive percolation conductive Li5AlO4 powder of Comparative Example 2 is shown.

[0086] from Figure 17 As can be seen, the first-charge specific capacity of the prepared lithium battery is only about 450 mAh / g at 4.6V. Compared with the original Li5AlO4 material, the modified material has a lower voltage plateau, while the first-charge specific capacity is higher and irreversible. This proves that trace amounts of sintering aids have a promoting effect on the crystal phase transformation and the synthesis of pure phase Li5AlO4.

[0087] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing an electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent, characterized in that, Includes the following steps: Pure phase Li5AlO4 was pre-polarized under an inert atmosphere. The pre-polarized pure phase Li5AlO4 was mixed with a cobalt source and boric acid was added as a grain boundary passivation aid. The mixture was then subjected to pulsed low-temperature plasma ball milling. The powder after pulsed low-temperature plasma ball milling was subjected to low-temperature crystal stabilization under micro-negative pressure to obtain the electric field-assisted plasma modified pressure-responsive percolation conductive pre-lithiation reagent. The pre-polarization polarization voltage is 450~600V, and the polarization time is 6~12min; The conditions for pulsed low-temperature plasma ball milling are: plasma discharge voltage 5~30kV, pulse current 10~100mA, frequency 5~10kHz, intermittent ball milling, and temperature ≤40℃ throughout the process. The conditions for low-temperature crystal stabilization under micro-negative pressure are: temperature 120~160℃, pressure -0.07~-0.03MPa, and heat preservation for 2~4h.

2. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 1, characterized in that, The pure phase Li5AlO4 was prepared by ball milling and sintering using lithium and aluminum sources as raw materials, combined with sintering aids.

3. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 2, characterized in that, The lithium source includes at least one of Li₂O, LiOH, LiOH·H₂O, Li₂CO₃, and LiNO₃; the aluminum source includes at least one of Al₂O₃, Al(OH)₃, and Al(NO₃)₃·9H₂O; the sintering aid is anhydrous lithium fluoride; the lithium-aluminum molar ratio of the lithium source to the aluminum source is 5.01~5.1:1; the amount of the sintering aid added is 0.15~0.6% of the total mass of the lithium source and the aluminum source; the ball milling media is zirconia balls, and the ball-to-material mass ratio is 8~15:1; the sintering is a three-stage sintering under an inert atmosphere, with a temperature gradient of 450℃ for 8~12h, 600℃ for 8~12h, and 800℃ for 60~80h.

4. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 1, characterized in that, The intermittent ball mill has a milling speed of 400~1400 rpm and a milling time of 3~24h, with a 5min stop after every 30min of milling.

5. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 1, characterized in that, The cobalt source includes LiCoO2, CoO, Co3O4, and LiNi. x Co y Al z O2 and LiNi x Co y Mn z At least one of O2; the LiNi x Co y Al z O2 and the LiNi x Co y Mn z In O2, 0.30≤x≤0.99, 0.01≤y≤0.40, and 0.00≤z≤0.

40.

6. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 1, characterized in that, The mass ratio of the pre-polarized pure phase Li5AlO4 to the cobalt source is 2~10:

1.

7. The preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent according to claim 1, characterized in that, The amount of boric acid is 0.05~0.3% of the total mass of the prepolarized pure phase Li5AlO4 and the cobalt source.

8. An electric field-assisted plasma-modified pressure-responsive percolation conductive prelithiation reagent prepared by the preparation method of the electric field-assisted plasma-modified pressure-responsive percolation conductive prelithiation reagent according to any one of claims 1 to 7.

9. A lithium-added positive electrode sheet, characterized in that, The components include a positive electrode active material and the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent as described in claim 8.

10. The application of the electric field-assisted plasma-modified pressure-responsive percolation conductive pre-lithiation reagent of claim 8 or the lithium-replenishing cathode sheet of claim 9 in the preparation of lithium batteries.